Implementing inflation targeting in Brazil: an institutional analysis - Strachman, Eduardo [UNESP] (My University, 2013)
The paper shows the advantages and handicaps of implementing an inflation target (IT) regime, from a Post-Keynesian and, thus, an institutional stance. It is Post-Keynesian as long as it does not perceive any benefit in the mainstream split between monetary and fiscal policies. And it is institutional insofar as it assumes that there are several ways of implementing a policy, such that the chosen one is determined by historical factors, as it is illustrated by the Brazilian case. One could even support IT policies if their targets were seen just as “focusing devices” guiding economic policy, notwithstanding other targets, as, in the short run, output growth and employment and, in the long run, technology and human development. Nevertheless, an IT is not necessary, although it can be admitted, mainly if the target is hidden from the public, in order to increase the flexibility of the Central Bank.

Mostram-se as vantagens e desvantagens da implementação de um regime de metas de inflação, de uma perspectiva pós-keynesiana e institucional. Pós-keynesiana pois não crê em benefício na separação entre políticas monetária e fiscal prescrita pelo mainstream. E institucional porque assume que há vários modos para implementar políticas; assim, o escolhido é determinado por fatores históricos, como ilustrado pelo caso brasileiro. Pode-se até apoiar metas de inflação, desde que estas sejam vistas apenas como “focusing devices”, guiando políticas, mas considerando outros objetivos, como, no curto prazo, o produto e o emprego e, no longo, o desenvolvimento tecnológico e humano. Ressalte-se que metas de inflação não são necessárias, apesar de serem admissíveis, sobretudo se mantidas escondidas do público, funcionando apenas como um foco e dando flexibilidade aos BCs.
Keywords: Brazil; Inflation; Inflation Targeting; Monetary Policy; Economic Policy; Central Bank; Banco Central; Brasil; Economia Pós-Keynesiana; Economia Keynesiana; Inflação; Metas de Inflação